(untitled) (American Journal of Pedagogical and Educational Research, 2024)
This article reflects on the duties and activities of a teacher of technical higher education, and that the main basis of pedagogical activity is the lesson. issues such as orientation to learning, interaction of pedagogue and students in the development of students’ creative abilities are highlighted.